Malaysian kitchen : explore the exquisite food and cooking of Malaysia, with 80 superb recipes shown step-by-step in more than 350 beautiful photographs - Basan, Ghillie; Tan, Terry (London, England : Southwater, 2010)
Malaysia is a region that has many distinct localized cooking styles which is reflected in the exciting food that can be enjoyed throughout the country. This title features 80 recipes that capture the fiery and sweet flavours of this region, and includes soups, snacks, rice and noodles, fish and shellfish, meat and poultry, salads and sweets
1. A culinary history of Malaysia -- 2. Malaysian cuisine today -- 3. Regional flavours -- 4. Celebrations and festivals -- 5. Traditional equipment -- 6. Cooking techniques -- 7. Broths and soupy noodles -- 8. Fried and grilled snacks -- 9. Rice and noodles -- 10. Fish and shellfish -- 11. Meat and poultry -- 12. Vegetables and salads -- 13. Condiments -- 14. Desserts and drinks
"Includes all the classic dishes from hot and sour fish soup and mixed seafood hor fun to malay lamb korma and mango and lime lassi"
Includes index
Keywords: Cookery, Malaysian; Cooking, Malaysian; Food and cooking of Malaysia and Singapore